The Effect Of Service Quality And Price On Customer Satisfaction At Aneka Motor Sepauk Workshop - Anastasia Agnes Anggy; Neni Triana M (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The automotive service industry continues to grow along with the increasing need for motor vehicles. This study aims to analyze the effect of service quality and price on customer satisfaction at the Aneka Motor Sepauk Workshop. The study used a quantitative method with an associative approach. Data were collected through questionnaires distributed to 100 workshop customer respondents. Data analysis was carried out using multiple linear regression. The results showed that service quality and price have a significant effect on customer satisfaction, both partially and simultaneously. Service quality including reliability, responsiveness, assurance, empathy, and physical evidence make a large positive contribution to customer satisfaction. Prices that are in accordance with benefits and competitiveness also have a significant impact on satisfaction. This study concludes that improving service quality and adjusting competitive prices are the keys to creating customer satisfaction at the Aneka Motor Sepauk Workshop.